El maravilloso regreso de Jacob Cerf - Miller, Rebecca, 1962- (Nuevos tiempos (Madrid, Spain), 2014)
An eighteenth-century Jewish peddler is reincarnated as a fly in present-day Long Island, and becomes involved in the lives of two residents.